Walk out walk on : a learning journey into communities daring to live the future now - Wheatley, Margaret J.; Frieze, Deborah (BK currents book., 2011)
Bestselling author Margaret Wheatley and long-time Berkana Institute collaborator Deborah Frieze take readers on a learning journey into seven diverse communities that have walked out of limiting beliefs and practices and walked on to something new. From Brazil to Ohio, they demonstrate how each of these communities made a conscious choice to develop a healthier, more resilient world based on the idea to "create with what we have."